A GNU radio based SDR RFID platform. (22nd December 2009) - Jamali, B.
Radio frequency identification (RFID) is a technology to store and retrieve information remotely using electromagnetic waves. RFID has enormous potential to change the way industries collect and manage information. Research in this area has been growing during the last decade. RFID communication protocols are not mature and are under constant change and improvement by authorities. As such, in order to improve performance of RFID systems, there is an urgent need for an open platform for development, implementation and optimisation of novel communication protocols. An open-source software-defined radio architecture based on GNU radio platform is well-poised to achieve these goals.